(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article presents a detailed comparative analysis of the terminological systems of the Uzbek and English languages. It examines their diachronic development, structural characteristics, and the current state of scholarly investigation within both linguistic contexts. Particular attention is given to the dynamic evolution of the Uzbek terminological corpus under the impact of globalization, as well as to the dominant function of English as a principal donor of international terminology. Drawing on a range of lexicographic resources and theoretical paradigms, the study reveals significant inconsistencies and gaps in the standardization of Uzbek terminology in contrast to the more highly codified and systematized English model. The results underscore the necessity for enhanced digital integration, as well as the implementation of a coherent and unified strategy for the formation and regulation of neologisms in the Uzbek language.